Using factor analysis in soil science : a tool to summarize information - A.M. Mokhtaruddin (The Malaysian Society of Soil Science, 2015)
Some soil qualities are quantified or evaluated by using many indices or by measuring many soil properties because these soil qualities are influence by many interacting soil factors. The information produced from such a variety of measurements can be summarized using the multivariate statistical tool called factor analysis. Factor analysis simplifies complex sets of data by representing them with fewer variables called common factors. This paper is to explain the fundamentals of factor analysis, its use and its interpretation. To illustrate factor analysis, secondary data was used to derive a single measure of soil tilth from the measurement of several soil properties. Data of five variables: humus, porosity (PORE), bulk density (BD), sand and clay content of twenty soil samples were re-analysed with the statistical program SPSS. Factor analysis summarized the information contained in those five variables into two common factors: the structure and consistency factors. The variables associated to the structure factor were humus, PORE and BD, and to the consistency factor were sand and clay. Thus, the measure of soil tilth is: Tilth index=structure index-\\consistency index\\ because the better the soil structure the better the soil tilth, but extreme values of consistency are detrimetal to soil tilth.